Inhibition of yeast‐to‐filamentous growth transitions in Candida albicans by a small molecule inducer of mammalian apoptosis. Issue 3 (29th November 2017) - Goffena, Joy; Toenjes, Kurt A.; Butler, David K.
Abstract: The opportunistic fungal pathogen of humans Candida albicans is able to grow in different morphological forms such as round or oval yeasts and filamentous hyphae and pseudohyphae. Morphogenesis, the ability to switch between the yeast and filamentous growth forms, is important for adapting to new microenvironments in the human host and for pathogenesis. The molecular pathways governing morphogenesis are complex and incompletely understood. Previously, we identified several small organic molecules that specifically inhibit the initiation of hyphal growth in C. albicans without affecting cell viability or budded growth. One molecule from that screen is known to induce apoptosis in mammalian cells. In this study, we have screened additional inducers of mammalian apoptosis and identified BH3I‐1, as well as several structural derivatives of BH3I‐1, that act as specific inhibitors of morphogenesis under a variety of environmental conditions. Chemical epistasis experiments suggest that BH3I‐1 acts downstream of the hypha‐specific gene regulators Rfg1, Nrg1 and Ume6.